Search
Ask a question
0

-17+4n=3(n-7)

I live in Pomona and i need help with my homework so I don't have a bad grade in school.

3 Answers by Expert Tutors

Tutors, sign in to answer this question.
William H. | SAT, ACT and other TutoringSAT, ACT and other Tutoring
2
The way you solve problems like this is use algebra to get the variable(in this problem n) on the left and the numbers on the right.
 
  1. The first step is to solve 3(n-7) which can use the distributive property to show that this equals 3(n) - (3)(7) which equals 3n - 21. This means the equation is now -17 + 4n = 3n - 21
  2. The next step is to add 17 to each side. This means that the equation is now 4n = 3n - 4
  3. Next we subtract 3n from each side leaving us with n = -4.
 
Therefore, the answer is n = -4.
 
Let me know if this is still unclear. I would be happy to explain it more.
Philip P. | Effective and Affordable Math TutorEffective and Affordable Math Tutor
5.0 5.0 (428 lesson ratings) (428)
1
-17 + 4n = 3(n-7)
 
First distribute (multiply) the 3 across the terms in teh parentheses:
 
-17 + 4n = 3*n - 3*7 = 3n - 21
 
Now add 17 to both sides:
 
+17 - 17 + 4n = 3n - 21 + 17
4n = 3n - 4
 
Now subtract 3n from both sides:
 
4n - 3n = 3n - 3n - 4
n = -4
 
Check:
-17 + 4n = 3(n-7)
Plug in n = -4:
-17 + 4(-4) = 3(-4-7)
-17 - 16 = 3(-11)
-33 = -33
CHECK!
Anthony B. | Physics/Math Tutor (3.9 Math/Science GPA); Here to help!Physics/Math Tutor (3.9 Math/Science GPA...
0
Distribute the 3 on the right side of the problem.......
 
-17 + 4n = 3n -21
 
Then solve for n by moving all non 'n's to one side.... for example..
 
4n-3n = -21 +17
 
Then it's simple math from there.